Jalan Swadaya Perumahan Bogor: Integrasi Desain Sirkulasi dan Resiliensi Iklim untuk Ruang Hidup Aktif - Agung Sugiarto (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The rapid pace of housing development in Bogor has created a gap with the provision of formal infrastructure, which has encouraged the emergence of community-led self-help road initiatives. While capable of addressing urgent connectivity needs, these road formations often ignore essential design standards, particularly those related to circulation and environmental context. This study focuses on a specific challenge in Bogor, namely high rainfall (